The everything guide to remote work : the ultimate resource for remote employees, hybrid workers, and digital nomads - Duffy, Jill (Stoughton, Massachusetts : Adams Media, 2022)
"During COVID-19, working from home became the new normal. Now, both employers and employees find that the remote work they were forced to adjust to may be, well, better-financially, sustainably, and even in terms of overall morale and productivity. But working from home is not without its challenges. It can be difficult to eliminate distractions, strike a solid work/life balance, and maintain social connections that are crucial in the workplace. Whether you're trying to find and land a job from the comfort of your home, learning to manage a virtual team, or dream of living a digital nomad lifestyle, The Everything Guide to Remote Work has everything you need to be successful. You'll learn to optimize your own workplace culture, whether it's in your home office or a constantly changing backdrop. So whether your company continues to work remotely full time or you only have to go to the office a few days a week, you'll be armed with all the tools you'll need to make the most out of this new lifestyle"--
Introduction -- Defining remote work -- Landing a remote job -- Setting up to work remotely -- Learning the art of remote communication - Etiquette for video and audio calls -- Understanding virtual collaboration and working on teams -- Remote work is reshaping meetings -- Maintaining productivity and avoiding distractions -- Establishing a solid work-life balance -- Ensuring growth as a remote employee -- Mastering the hybrid model -- Becoming a digital nomad -- How to participate in remote company culture -- Preparing for the future of remote work.
Includes bibliographical references and index.
110224
Keywords: Telecommuting; Virtual work teams; Home labor; Work-life balance; Handbooks and manuals; Self-help publications